The History of Sunan Bonang Mandala in The Lasem Chronicle (Carita Lasem) - Fahmi, Muhammad Nabil; Anggarini, Ida Fitri; Hoque, Obaidul (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This article aims to reveal the existence and origins of the establishment of the Sunan Bonang Mandala as narrated in the Carita Lasem text or the Lasem Chronicle. This descriptive-qualitative research employs content analysis methods to analyze the content and socio-historical context within the Lasem Chronicle text. Through content analysis and comparison with other historical data, this research concludes the strong hypothesis of the existence of the Sunan Bonang Mandala in Bonang Village, Lasem District, Rembang Regency. Sunan Bonang. As local historiography, the Lasem Chronicle shows the existence of an Islamic educational center led by Sunan Bonang in the 15th century AD. This text also emphasizes Sunan Bonang's position as a state saint whose missionary territory covers the areas of Tuban, Lasem, and their surroundings. Furthermore, the origins of the establishment of the Sunan Bonang Mandala in the Lasem Chronicle also depict a pattern of Islamic Mandala establishment during the Wali Songo period, where the establishment of Mandala is inseparable from the role of local sovereigns, simultaneously illustrating a positive pattern of sovereign-religious leader relations in the Islamization process in the Nusantara.